Effectiveness of administering tranexamic acid to high-risk hip and knee arthroplasty patients: a systematic review protocol. Issue 8 (8th August 2020) - Yapa, Shanil; Lockwood, Craig; Kuster, Markus
ABSTRACT: Objective: The objective of this review is to assess the safety and effectiveness in administering tranexamic acid in high-risk hip and knee arthroplasty patients. Introduction: Arthroplasty surgery is associated with a significant amount of perioperative blood loss. Tranexamic acid is an antifibrinolytic used to counteract blood loss. Although various studies have demonstrated the effectiveness of tranexamic acid without significant adverse effects, a majority of these studies have excluded high-risk patients. Due to this selection bias there is a lack of clear evidence of the safety of administering tranexamic acid in high-risk patients. Inclusion criteria: This review will consider studies that included high-risk patients aged >18 years who had previous myocardial infarction including cardiac stents, deep vein thrombosis and/or pulmonary embolism, transient ischemic attacks and/or stroke and clotting disorders. No exclusions will be made for the dosing route of tranexamic acid. The outcomes measured will be 1) thromboembolic complications of deep vein thrombosis, pulmonary embolism, transient ischemic attacks, stroke, myocardial infarction and death; 2) requirements of blood transfusion and 3) the amount of blood loss. Methods: A search will be conducted in PubMed, Embase, Scopus and Web of Science databases with the results being reported in a PRISMA flow diagram. Selected studies will be critically appraised by two independent reviewers for methodological quality. Study and outcome quality will be reported using the GRADE approach. Data will be extracted using a standardized data extraction tool. Studies will, where possible, be pooled in statistical meta-analysis. Effect sizes will be expressed as either odds ratios (for dichotomous data) or standardized mean differences (for continuous data) and their 95% confidence intervals will be calculated for analysis.